Tindak Tutur Direktif dalam Interaksi Pembelajaran Bahasa Indonesia di SMP Negeri 3 Gianyar, Bali - Ni Komang Diah Restu Swari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to describe the types and functions of directive speech acts found in Indonesian language learning interactions at SMP Negeri 3 Gianyar. Employing a descriptive qualitative research design, the data were obtained through note-taking and recording of teacher–student interactions during classroom activities. The analysis followed four main stages: data reduction, data collection, data display, data interpretation, and conclusion drawing. Directive speech acts, which are utterances intended to prompt the listener to perform a specific action, are an essential component of classroom discourse, as they directly influence student participation, classroom management, and instructional clarity. The findings reveal a total of 109 directive speech act utterances produced by both teachers and students. These utterances are categorized into six types: 18 requests, 52 questions, 22 commands, 3 prohibitions, 10 permissions, and 4 pieces of advice. Each type of directive speech act is used to achieve specific communicative purposes. Further analysis identified 11 distinct functions realized within these utterances, namely: requesting, inviting, pleading, asking, wishing, demanding, directing, instructing, prohibiting, permitting, and advising. For instance, teachers predominantly employed questioning and commanding functions to guide learning processes, check comprehension, and maintain classroom order, while students tended to use requesting and asking functions to seek clarification or assistance. The results of this research highlight the significant role of directive speech acts in facilitating interactive and goal-oriented communication in the language learning environment. Understanding the types and functions of such speech acts can provide valuable insights for educators in designing effective communication strategies that foster active learning, encourage student engagement, and create a positive classroom atmosphere. This study contributes to the broader field of pragmatics and educational linguistics by emphasizing the practical application of speech act theory in Indonesian language teaching contexts.